Delivered into covenant: pivotal moments in the book of Exodus, part two - Brueggemann, Walter (Pivotal moments in the Old Testament, 2021)
The book of Exodus brims with dramatic stories familiar to most of us: Moses' ringing proclamation to Pharaoh to "let my people go," the freed Israelites astonished by manna in the wilderness, God's descending on Mount Sinai in a cloud of fire and glory to deliver the law to Moses and the people. These signs of God's liberating agency, provision, and covenant have sustained oppressed peoples over the ages. But Exodus is also a complex book, which is why we divide it into two parts. Readers of parts one and two of Pivotal Moments in the Book of Exodus will encounter multilayered narratives about the mysterious action of the divine to overturn exploitative systems, the giving of a new law meant to set the people of Israel apart, and instructions for building a tabernacle in which God will dwell in glory. How does a contemporary reader make sense of it all? In Delivered into Covenant, Walter Brueggemann offers a guide to the second half of Exodus--from Israel's journey through the wilderness to Mount Sinai to the establishment of the tabernacle--drawing out "pivotal moments" in the text. Throughout, Brueggemann shows how Exodus consistently reveals a God who is in radical solidarity with the powerless and who is dedicated to cultivating a covenant people who act to repudiate the powers of empire. Questions for reflection and discussion are included at the end of each of the fourteen chapters, making it ideal for individual or group study